Lichens used in the Traditional Medicine by the Pankararu Indigenous Community, Pernambuco - Brazil (Global Journal of Science Frontier Research, 2018)
This is the first report of use of lichens as medicament in Brazilian semi-arid. Active compounds were found in lichens used by Pankararu people.
Keywords: health disorders; traditional phytotherapy; pharmacological research